Adversity Quotient Mahasiswa Tunanetra - Wieda Fikriyyah; Maya Fitria (University of Merdeka Malang, 2015)
This study aims to determine adversity quotient of students with disabilities (blind) in resolving and overcoming difficulties while studying in college. The informants are three visually impaired students who are already taking classes for four semesters and follows the student college organization. This study used qualitative methods of phenomenology. The data in this study comes from the words and actions of informants obtained by using observation and interviews. The data analysis used coding techniques. Results from this study indicate adversity quotient obtained from the collaboration of the four dimensions of adversity quotient, which is control, origin and ownership, reach, and endurance. Adversity quotient students with disabilities (blind) are influenced by internal and external motivational factors, perseverance, learning, risk taking behavior, competitiveness, and independence. In addition, a sense of gratitude for the conditions experienced, the experience of all the difficulties, and extensive network of friends also affects their adversity